Farrowing interval and pig performance - J D Wheat; M S Suba; A D Dayton; G L Allee; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1983)
The average for 1813 farrowing intervals was 16.78 minutes with a standard deviation of 25.37 minutes. Farrowing duration averaged 141.51 minutes, ranging from 11 to 618 minutes. The difference between farrowing intervals for Yorkshire and Yorkshire-Duroc crossbred dams was nonsignificant. Neither season of the year, birth order, sire of the litter nor sex of the pig significantly affected farrowing interval. However, dam of the litter affected farrowing interval in both groups, Yorkshires (P<.05) and crossbreds (P<.01), as did birth weight (r=.17, P<.0l). Number of pigs born alive and average farrowing interval for the dam were correlated negatively (r=-.39, P<.0l), while the correlation between farrowing duration and number of pigs born alive was .22 (P<.0l). Consequently, sow producti vity index was related negatively with average farrowing interval (r=-.30, P<.0l), but the correlation between farrowing duration and sow productivity index was .16 (P<.05).; Swine Day, Manhattan, KS, November 10, 1983
Keywords: Swine day; 1983; Kansas Agricultural Experiment Station contribution; no. 84-174-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 442; Swine; Farrowing; Performance